Trial and Error? Reelection Concerns and Policy Experimentation during the U.S. Welfare Reform - Andreas Bernecker; Pierre C. Boyer; Christina Gathmann (Institute for the Study of Labor (IZA), 2015)
We study the political economy of policy innovations during the U.S. welfare reform in 1996. Specifically, we investigate how reputation concerns among governors influence the decision to experiment with welfare policies. In line with a political agency model, our empirical results suggest that governors with high reputation among the electorate are less likely to experiment with welfare policies than governors with low reputation. Yet, governors with high reputation who are less concerned about reelection actually experiment more than governors striving for reelection. Overall, our findings imply that reelection concerns may inhibit innovation in the public sector.
Keywords: I38; H11; H77; D78; D83; 330; policy innovation; reputation concerns; U.S. welfare reform; experimentation; reelection concerns